Treatment of Cervicofacial Actinomycosis: A report of 19 cases and review of literature - Moghimi, Meshkan (Medicina Oral S.L., 2013)
Objectives: Actinomycosis is a chronic suppurative granulomatous infection caused by the Actinomyces genus. Orocervicofacial actinomycosis is the most common form of the disease, seen in up to 55% of cases. All forms of actinomycosis are treated with high doses of intravenous penicillin G over two to six weeks, followed by oral penicillin V. Large studies on cervicofacial actinomycosis are lacking. Therefore proper guidelines for treatment and treatment duration are difficult to establish. The aim of this study is to establish effective treatment and treatment duration for orocervicofacial actinomycosis. Study design: A Pubmed and Embase search was performed with the focus on treatment and treatment duration for cervicofacial actinomycosis. The hospital records of all patients presenting to our department with head and neck infection from January 2000 to December 2010 were reviewed, retrospectively. The following data were collected: age, gender, clinical presentation, aetiology, duration of symptoms, microbiological findings, treatment, and duration of treatment. The treatment and treatment duration is subsequently compared to the literature. Results: The literature search provided 12 studies meeting the inclusion criteria. All studies were retrospective in nature. Penicillin or amoxicillin/clavulanic acid are the preferred antibiotic regimens found in the literature. Most of our patients were treated with a combination of penicillin G 12 million units/day and metronidazol 500 mg 3/day, most commonly for a duration of 1 – 4 weeks, being shorter than the 3 – 52 weeks reported in the literature. Conclusion: When actinomycosis is suspected, our review has shown that a surgical approach in combination with intravenous penicillin and metronidazol until clinical improvement is seen, followed by oral antibiotics for 2 – 4 weeks is generally efficient. Key words:Actinomycosis, actinomyces, actinomycosis treatment, cervicofacial infection, actinomycosis diagnosis, head and neck infection.